1-ohm Impedance Criterion for Diagnosis of Single-Phase Ground Fault of Transmission Line - Xueming Zhou; Xiankang Wang; Yao Yao; Zhiqiang Feng; Zixuan Hu; Jianjin Fu; Zijian Li (IEEE Access)
The transition resistance during single-phase grounding faults in transmission lines is closely related to the fault cause. Quickly determining the cause of the fault through the transition resistance value and taking targeted measures to restore the power supply quickly is of great significance to improving the stability of the power system. Starting from the basic circuit principle, this paper analyzes the composition of the transition resistance for two typical grounding situations: the line-to-tower discharge and the line-to-ground discharge, and derives the equivalent impedance of the tower-wire grounding system. Based on analyzing the grounding wire parameters, the tower grounding resistance, and the span size, the 1-ohm impedance criterion was proposed, that is, the transition resistance during line-to-tower discharges should be less than 1 ohm. Then, the equation for calculating the transition resistance using the double-terminal fault recording was derived and simplified for engineering calculation. Finally, combined with 56 real fault cases of 220 kV~1000 kV transmission lines, each case’s transition resistance value and fault cause are analyzed to verify the effectiveness of the proposed 1-ohm criterion.